1997
DOI: 10.1093/ajcn/66.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Taste responses to naringin, a flavonoid, and the acceptance of grapefruit juice are related to genetic sensitivity to 6-n-propylthiouracil

Abstract: Increased consumption of vegetables and fruit has long been the focus of dietary strategies for disease prevention. Some vegetables and fruit have bitter tastes, which can be aversive to consumers, particularly children. The present study tested the hypothesis that acceptance of grapefruit juice is influenced, in part, by sensitivity to the bitter taste of 6-n-propylthiouracil (Prop), a heritable trait. A sample of 123 women, mean age 28 y, was divided into nontasters (n = 39), tasters (n = 49), and supertaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 36 publications
2
87
1
Order By: Relevance
“…Observations in adults that PROP tasters perceive greater oral intensity from a wide range of compounds, including bitter (39,64), sweet (65,142), and fat (46,65,110,131), provoked the possibility that the PROP phenotype might serve as a marker of dietary intake with important nutritional implications. Interest in the potential association between taste sensitivity to bitter thiourea compounds like PROP and dietary patterns grew from data from surveys conducted in adult populations by Fischer and colleagues (53) and Glanville & Kaplan (57).…”
Section: Prop Phenotype As a Marker For Eating Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations in adults that PROP tasters perceive greater oral intensity from a wide range of compounds, including bitter (39,64), sweet (65,142), and fat (46,65,110,131), provoked the possibility that the PROP phenotype might serve as a marker of dietary intake with important nutritional implications. Interest in the potential association between taste sensitivity to bitter thiourea compounds like PROP and dietary patterns grew from data from surveys conducted in adult populations by Fischer and colleagues (53) and Glanville & Kaplan (57).…”
Section: Prop Phenotype As a Marker For Eating Behaviorsmentioning
confidence: 99%
“…Plant foods are the most common source of bitter-tasting compounds in the diet, and the majority of plants are capable of synthesizing bitter compounds for protection against predators (25,51). Tasters have been hypothesized to have lower acceptance and intake of bitter-tasting fruits and vegetables (e.g., grapefruit juice, cruciferous vegetables) on the basis of early studies demonstrating a positive association between PROP taste sensitivity and perceived bitterness in compounds, such as caffeine (90), quinine (64), and naringin (the bitter compound in grapefruit) (39). These findings could have important health implications because many of the bitter-tasting compounds in foods (e.g., flavonoids, phenols, glucosinolates) are anticarcinogenic.…”
Section: Bitter-and Strong-tasting Foodsmentioning
confidence: 99%
“…7 for review) distinguished only between PROP tasters and nontasters, new research has identified non-tasters, regular tasters and supertasters of PROP. Those distinctions were based on PROP detection thresholds and the magnitude of bitterness ratings for more concentrated PROP solutions 18,21,22 . Supertasters, most of whom are said to be women, on average had more fungiform papillae and a higher density of taste buds per papilla than did either regular tasters or non-tasters of PROP 23 .…”
mentioning
confidence: 99%
“…PTC or PROP sensitivity was linked to a greater number of dislikes for green and cruciferous vegetables (cabbage, Brussels sprouts, spinach and kale), rhubarb, sauerkraut, beer, coffee, brown bread and various sharp cheeses 20,25,26 . More recent studies have linked PROP taste responsiveness to reduced acceptance of naringin solutions, soy products and Japanese green tea 22,27 . The latter studies are particularly relevant to the cancer prevention literature, given that many of the antioxidant phytochemicals are said to be found in green and cruciferous vegetables, soy products, citrus fruit and tea 28,29 .…”
mentioning
confidence: 99%
“…Those bitter tastants that can safely be administered to the human gastrointestinal tract in adequate quantities (e.g., quinine and naringin) have also been reported to be rated less bitter by those who cannot taste PTC compared with those who can (6,7). This raises the possibility that genotypic differences in responsiveness to bitter tastants might also exist in the gastrointestinal tract.…”
mentioning
confidence: 99%